Faktor-Faktor yang Mempengaruhi Perilaku Konsumen terhadap Keputusan Pembelian di Pusat Pasar Kota Medan - Datubara, Maryono; Tarigan , Eka Dewi Setia (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Competition between traditional and modern markets requires market managers to understand the factors that influence consumer purchasing decisions. This study aims to analyze the influence of social, personal, and psychological factors on consumer purchasing decisions at the Medan City Market Center. This study uses a quantitative approach with an associative method. The research sample consisted of 96 respondents who were analyzed using multiple linear regression. Based on the partial test results, social factors have a positive and significant effect on purchasing decisions with a significance value of 0.012 < 0.05 and a t-value of 2.554 > t-table 1986. Personal factors also have a positive and significant effect with a significance value of 0.000 < 0.05 and a t-value of calculated t-value of 33.634 > t-table 1.986. Psychological factors also have a positive and significant effect with a significance value of 0.000 < 0.05 and a t-value of 31.796 > t-table 1.986. Simultaneously, social factors, personal factors, and psychological factors have a significant effect on purchasing decisions with a significance value of 0.000 < 0.05. The results of the coefficient of determination test show an Adjusted R Square value of 0.976, which means that 97.6% of the variation in purchasing decisions can be explained by these three variables.